Aplicación móvil para la gestión de información de lecturas del consumo de agua potable del gad municipal de Latacunga. - Caiza Toaquiza, Jairo René (2019)
In the unit of commercialization of drinking water of the city hall in Latacunga (GAD-DIMAPAL), it could find different problems for taking the reading of water. The lack of technological tools which not allowed speed up the work. Compiled the lectors, the media that usually printed forms that fill manually thought that the assignment of the routes the lectors, so the information collected on occasions were not correct, also the routes was not traveled entirely, registering non-real data and this caused problems at the moment the digitized the printed forms. For this reason, it was proposed to develop mobile application management of drinking water readings in order to optimize the time it takes to collect data from meters and digitize the readings provided by the water readers, having greater control the routes assigned to each reader. However of the respective interviews with the interested parties the functional requirements for the application could be obtained, the Scrum methodology subsequently used for the project management process, which made it easier to develop the functionalities using Sprints, therefore, tests also applied at the black box level in order to verify the functionality of the application. As a result of the application, the direct digitization of readings obtained and the generation of an excel file of reading records, to complement this, it can be concluded that there was a decrease in the time taken to take readings from the water meters of the different users, in turn allowing real data to obtain. The primary beneficiaries of this application are the digitizers and readers, together with the control of the administrative staff of DIMAPAL.